Artemisinin Content in Artemisia scoparia - Renu Sarin, Aditi Singh* (Recent Research in Science and Technology, 2010)
Artemisinin is considered as the natural, active and potent antimalarial drug Artemisia annua Linn. is the only known source for the production of artemisinin reported till date. An attempt was made on a perennial faintly odoratus herb, A. scoparia Waldst et Kit. to find out an alternative of A. annua for the production ofÂ artemisinin. Generation of hairy roots was also tried wih an attempt to increase the concentration of artemisinin in the biofactories. In the present investigation A. scoparia was shown to contain artemisinin